Análisis de factibilidad para la fusión de la Empresa Pública Metropolitana de Gestión Integral de Residuos Sólidos, EMGIRS EP y la Empresa Pública Metropolitana de Aseo, EMASEO EP, para realizar la gestión de los residuos sólidos en la ciudad de Quito - Peñaherrera Sarmiento, Gonzalo Enrique (2018)
In this investigative work is analyzed and determines the feasibility of merging two public companies using the absorption process, as a strategy of optimization of State resources, establishing an efficient and effective management model to optimize resources economic and human talent. Based on analysis of the legislation and regulations governing the operation of public companies EMGIRS EP and EMASEO EP; as well as, from its strategic plans and management models, the impact that the proposed merger model would have on its operations and administrative activities was determined, proposing a new organizational chart by processes that would optimize the personnel to comply with the established goals and objectives.